Nitrogen doped graphene quantum dots modified a crystalline zinc phosphite based non-enzymatic electrochemical sensor for the ultra-low detection of tyramine - Pi-Chen Wei; Asit Kumar Panda; Yu-Chung Chang; Yi-Rong Li; Todd Hsu; Chih-Min Wang (Food Control, 2026)

Assessing 3-D variability of ultrafine particle using a Geo-AI modelling approach: A case study in Zhunan-Miaoli, Taiwan - Chia-Wei Hsu; Yinq-Rong Chern; Jun-Jun Su; Pei-Yi Wong; Aji Kusumaning Asri; Candera Wijaya; Yu-Cheng Chen; Shih-Chun Candice Lung; Ta-Chih Hsiao; Tee-Ann Teo; Yi-Liang Shih; Chih-Da Wu (Environmental Pollution, 2025)

Innovating Taiwan's greenhouse gas estimation: A case study of atmospheric methane using GeoAI-Based ensemble mixed spatial prediction model - Hao-Ting Chang; Yinq-Rong Chern; Aji Kusumaning Asri; Wan-Yu Liu; Chin-Yu Hsu; Ta-Chih Hsiao; Kai Hsien Chi; Shih-Chun Candice Lung; Chih-Da Wu (Journal of Environmental Management, 2025)

Synergistic properties of single-component hexagonal iron borate for superior and sustainable photo-Fenton catalysis - Po-Yi Wu; Jing-Cheng Hsu; Tsung-Yueh Lin; Yu-Lun Zhu; Yu-Rong Chang; Pei Yuin Keng (Journal of Environmental Chemical Engineering, 2025)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

Climate change-induced impacts on PM2.5 in Taiwan under 2 and 4 °C global warming - I-Chun Tsai; Pei-Rong Hsieh; Huang-Hsiung Hsu; Yu-Shiang Tung; Yung-Ming Chen; Chao-Tzuen Cheng (Atmospheric Pollution Research, 2024)

In vitro and in vivo protective potential of quercetin-3-glucuronide against lipopolysaccharide-induced pulmonary injury through dual activation of nuclear factor-erythroid 2 related factor 2 and autophagy - Pei-Rong Yu; Chiao-Yun Tseng; Cheng-Chin Hsu; Jing-Hsien Chen; Hui-Hsuan Lin (Archives of Toxicology, 2024)

The effect of isovitexin on lipopolysaccharide-induced renal injury and inflammation by induction of protective autophagy - Chiao-Yun Tseng; Pei-Rong Yu; Cheng-Chin Hsu; Hui-Hsuan Lin; Jing-Hsien Chen (Food and Chemical Toxicology, 2023)

Impacts of 2 and 4°C global warmings on extreme temperatures in Taiwan - I‐Chun Tsai; Pei‐Rong Hsieh; Chao‐Tzuen Cheng; Yu‐Shiang Tung; Lee‐Yaw Lin; Huang‐Hsiung Hsu (International Journal of Climatology, 2023)
Extreme temperatures were considered natural hazards because they could increase morbidity and mortality. Understanding the extreme temperature changes at different warming levels is crucial to climate change mitigation and adoption for human health. This study projected climate change effects on the intensity, occurrence, and duration of extreme temperatures in Taiwan with 2 and 4°C global warming scenarios using the Weather Research and Forecasting model. The future climate simulations were conducted with the pseudo‐global warming approach, and the future climate changes were obtained from the ensemble mean of simulations in the Coupled Model Intercomparison Project 5. The simulated daily mean temperature increased by 1.40 and 3.09°C under 2 and 4°C global warmings. In a warming world, the daily maximum temperature was projected to increase by 1.35–3.00°C, whereas the daily minimum temperature was even higher, leading to weaker diurnal temperature variation in most regions. The simulation results show that intensified heatwaves with frequent and prolonged durations become par for the course, whereas extremely cold days disappear gradually. The occurrence of heatwaves in the future is projected to be five times that in the current climate. Comparing the global warming impacts over different land‐use types, the heatwave occurrence over urban areas rose more quickly than over other land‐use types; forests are less vulnerable to global warming. On the contrary, the changes in extremely cold days over urban areas were weaker than over other land‐use types. Overall, the effects of global warming on temperature revealed that extreme events were more severe with increased temperature than with the mean state of air temperature. Nonlinear behaviours indicated that global warming should be limited to 2°C, and the additional 2°C warming (from 2 to 4°C) should be addressed carefully.

Insights into the α-amylase and α-glucosidase inhibition mechanism of 4-(4-hydroxyphenyl)-but-3-en-2-one from Scutellaria barbata D. Don: enzymatic kinetics, fluorescence spectroscopy and computational simulation - Bongani S. Dlamini; Chiy-Rong Chen; Wen-Ling Shih; Yu-Kuo Chen; Jue-Liang Hsu; Chi-I Chang (Medicinal Chemistry Research, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Relationship Between Body Composition and Balance Performance in Older Adults with Hyperkyphosis - Phunsuk Kantha; Shiow-Chwen Tsai; Chien-Wen Hou; Rong-Sen Yang; Pei-Yu Su; Wei-Li Hsu (Journal of Medical and Biological Engineering, 2021)

Development and characterization of novel microsatellite markers in chestnut tiger butterfly Parantica sita (Lepidoptera: Nymphalidae) using next-generation sequencing - Ping Hu; Chia-Lung Huang; Min-Xin Luo; Yu-Feng Hsu; Rong-Jiang Wang (Applied Entomology and Zoology, 2020)

Unexpected dose response of HaCaT to UVB irradiation - Rong-Shing Chang; Chi-Shuo Chen; Ching-Lung Huang; Chiu-Ting Chang; Yujia Cui; Wei-Ju Chung; Wun-Yi Shu; Chi-Shiun Chiang; Chun-Yu Chuang; Ian C. Hsu (In Vitro Cellular & Developmental Biology - Animal, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Expression of a gene encoding a rice RING zinc-finger protein, OsRZFP34, enhances stomata opening - Kuo-Hsuan Hsu; Chia-Chin Liu; Shaw-Jye Wu; Ying-Yu Kuo; Chung-An Lu; Ching-Rong Wu; Pei-Jyun Lian; Chwan-Yang Hong; Yi-Ting Ke; Juin-Hua Huang; Ching-Hui Yeh (Plant Molecular Biology, 2014)

Direct analysis of tobacco-specific nitrosamine NNK and its metabolite NNAL in human urine by LC–MS/MS: evidence of linkage to methylated DNA lesions - Chiung-Wen Hu; Yu-Wen Hsu; Jian-Lian Chen; Lai-Man Tam; Mu-Rong Chao (Archives of Toxicology, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Molecular identification and antibiotic control of endophytic bacterial contaminants from micropropagated Aglaonema cultures - Jong-Yi Fang; Yu-Rong Hsu (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Characterization of the role of protein–cysteine residues in the binding with sodium arsenite - Yu-Ying Chang; Tai-Chih Kuo; Chun-Hua Hsu; Duen-Ren Hou; Yung-Hsi Kao; Rong-Nan Huang (Archives of Toxicology, 2012)